Developing a reduced consumer-led lexicon to measure emotional response to beer - Chaya, Carolina; Eaton, Curtis; Hewson, Louise; Fernández Vázquezc, Rocío; Fernández-Ruiz, Virginia; Smart, Katherine A.; Hort, Joanne (Elsevier, 2015)
Previous researchers have recently recommended and utilised consumer-led lexicons to measure emotional response. This study further advances this approach by 1) making the lexicon generation process more efficient by using consumer focus groups as opposed to individual consumer interviews and 2) decreasing the number of responses required from each consumer by reducing the lexicon to categories of similar terms. In response to 10 lager samples which were manipulated in order to control selected sensory properties, focus groups generated a lexicon of 44 emotion terms. This lexicon was reduced to 12 distinct emotion categories using linguistic checks and cluster analysis. Naïve beer consumers (n = 113) used these 12 emotion categories to rate their emotional response to the 10 samples. The reduced consumer-led lexicon was validated through its ability to discriminate across samples as well as show differences in emotional response between genders and age groups. The 12 emotion categories were found to discriminate well between samples, although a number of categories grouped samples similarly. However, differences in responses to otherwise comparable emotion categories were identified between genders and age groups, highlighting the importance of including all emotion categories so as to not over-reduce the lexicon and risk missing out on valuable emotion data.